Effective removal of nitrate by denitrification re-enforced with a two-stage anoxic/oxic (A/O) process from a digested piggery wastewater with a low C/N ratio. (15th June 2019) - Chen, Jinliang; Xu, Yanbin; Li, Yuxin; Liao, Jinsong; Ling, Jiayin; Li, Jiayi; Xie, Guangyan
Abstract: The combined process of a long-term biogas digester and double anoxic/oxic tanks is very commonly used in piggery wastewater treatment in South China, but the effluent does not meet the discharge standard of total nitrogen (TN) and chemical oxygen demand (CODCr ) due to a low C/N ratio and insufficient organic carbon in digested piggery wastewater. Thus, a typical two-stage anoxic/oxic (A1/O1/A2/O2) process, which is widely used to treat digested piggery wastewater in the engineering application, was selected for study on a laboratory scale. Finally, the average removal efficiency of ammonia nitrogen in the two-stage AO process was 98.7%; at the same time, the content of nitrate increased to 180–190 mg/L. To further eliminate nitrogen, an anaerobic tank (S1), which was equipped the sludge that was acclimated in our laboratory by a high nitrogen loading slurry, was employed to treat the effluent from the two-stage AO process and contributed more than 70% removal efficiency. Further analysis showed that ammonia-oxidizing bacteria (AOB) and nitrite oxidizing bacteria (NOB) in the O1 and O2 tanks together contributed to the conversion of ammonia nitrogen to nitrate, but the process of heterotrophic denitrification was inhibited in the A1 and A2 tanks because of insufficient carbon sources. In addition, most of the nitrate concentration was reduced under conditions with insufficient carbon sources, while Thauera -dominated the bacterial population in the sludge sample of the S1 tank. Graphical abstract: Image 1 Highlights: Advanced denitrification was performed for digested piggery wastewater. 73% Nitrate was removed by the acclimated sludge under a low C/N ratio conditions. Most of nitrogen removal genera were positively correlated with each other. Thauera contributed significantly on denitrification in the stimulated process.